FORMAÇÃO DE PROFESSORES NAS MODALIDADES DE EDUCAÇÃO A DISTÂNCIA E PRESENCIAL: REPRESENTAÇÃO SOCIAL DE ALUNOS SOBRE AS MODALIDADES DE ENSINO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Taking into consideration the teaching context, in which teachers and students are mediated by technological resources, not using the conventional classroom but employing the virtual learning environment (VLE) we reflected on the education modes of delivery issue. The research problem raised the following question: which are students’ Social Representations of Distance and Classroom taught courses? From this question, we started the research which aimed to point out, through analytical reflections, the students’ Social Representations of these education modes of delivery. The study was developed at the Ponta Grossa State University, in the courses Teaching Physical Education, Education, Language and Mathematics which are offered in both modes Distance and Classroom courses. In order to answer our question and achieve our objective, we carried out qualitative research, since we understand that this is the most suitable methodology to this study. For the collection of empirical data, a questionnaire was used, which was applied both in a printed version and online. The theoretical background was based on the Social Representations Theory (SRT) by Sergé Moscovici (1976), since this is a theory related to the common sense knowledge study, which characterizes a set of explanations, beliefs and ideas that enable us to evoke a certain event, person or object. The SR is related to the way the individual thinks and interprets their own everyday life, that is, it is formed by the set of images of a reference system that allows the individual to interpret the information received, reinterpreting their life and giving it some meaning. In order to aid the data analysis, the methodology used was that proposed by Bardin (1977). The results pointed out that there are different SR between students who have classroom taught courses with online subjects and those that have only classroom courses and Distance course students. We emphasize that the SR about time, flexibility, negligence, effort, autonomy, dedication, opportunity and technology are common to all responses given by the teaching courses students participating in the study.
Teacher education through distance and classroom courses: Students’ social representations of teacher education
Keywords: educação a distância; teoria das representações sociais; modalidades de ensino; distance education; social representations theory; education modes of delivery; CNPQ::CIENCIAS HUMANAS::EDUCACAO